PEMBERDAYAAN GURU MIS PASUNDAN KECAMATAN MADANG SUKU I DALAM PENGUATAN BUDAYA SEKOLAH BERBASIS MISI PAI - Coirun Niswah; Rabbul Izzatin; Zuhdiyah Zuhdiyah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2020)
This research-based devotion is done in order for the teachers of MIS Pasundan District Madang People I District Oku East Sumatera Selatan can strengthen the school culture based PAI mission by realizing the values of religious teachings as a tradition in the behavior and culture of the organization that is attended by the entire school citizen. The model of devotion implemented is a research-based dedication using the school Action Research (PTS) approach, namely planning (action), observation (observe), and reflection (reflect). The results obtained that has been a strong school culture in MIS Pasundan on the form of physical manifestations of the original has not cultured the score 185 become already culture score 359, on the form of behavioral manifestations from the original has not cultured the score 5511 to already cultured the score 887, and on the form of the value manifestation of the original not yet cultured 194 scores became already As well as the increased activity of teachers on school culture in MIS Pasundan, which is the re-activation of the teachers in FGD activities only ranging from 61, 07%, increased to 78.94% on training activities, and the activity of the teacher increased again to 87.86% in the activities of the school culture movement in MIS Pasundan East OKU.